Information Supermarkets in the Context of Community Information Services - Mohan, Vishwa (DESIDOC Journal of Library & Information Technology, 2003)
Community information (CI) is an umbrella concept. It can be described as 'survival information’; hence the scope of CI will be proportionate to the numerous ways and means of survival of the members of the community. There is a need for controlling and institutionalisation of CI services. 'Information Supermarkets' in the context (3f CI which could be called as 'CI Supermarkets' (CISMs). This would ensure the availability of CI at 'one stop' information supermarkets to suit the information seeking behaviour of the modern customers. The paper discusses the need for information supermarkets in general and the ClSM in particular, describing the nature and scope of CI. It briefly presents the important features of CISMs. The author opines that, with the emergence of Internet and Intranets, the concept of CISM will be a reality in near future. http://dx.doi.org/10.14429/dbit.19.1.3457